A Study on Folk Culture of the Mising Community in North-East India - Gogoi, Bhupen; Chetia, Maghali (International Journal of Psychosocial Rehabilitation, 2020)
Assam is a multilingual state of India including different castes and tribes. The Misings are the second  large tribe of Assam. Their folk-life is full of vivid art and culture. Culture provides the introduction of a caste or a  tribe. The ethnic image of a tribe or caste is reflected through their cultural features. Acculturation, assimilation,  Sanskritization and modernization have played a major role in the changing of the culture and lifestyle of the Mising  community. They have deviated from their original source and have acquired a modern form today. Yet, the  different side of their folk-culture is changing in the stream of time. As a result of the spread of science and  development, like other tribes, the Mising folk-belief and folk-life are also changing. Due to these effects, social and  mantel changes of common life are taking place in all directions. It is very important to collect and compile the past  the Mising community way of life before it becomes completely dissected. Therefore it is very important to study,  preserve, and spread the culture and folk-life of the Mising tribe. This study will discuss an introduction to the folk  culture of the Mising tribe of Northeast India and the impacts of globalization, acculturation, assimilation and  modernization in their folk culture.